(untitled) (Impetus, 2022)
Introduction: This investigative work was developed on the progress of the physical preparation, technical, tactical preparation and coordination capacities of the sub 12 category of Club Choachí F.C. Objective: To acquire experience in the space of the sports training, and also, to contribute in the preparation and technical-tactical training of the category SUB / 12 in the minor divisions of Choachí FC, looking for an improvement in the sports performance. Methodology: Of specific works, generating a development of coordinative skills, technique and tactics in football, with a mixed approach, because it will have qualitative and quantitative elements, using human and material resources, as professionals in the area of sport and football field. Result: This practice one of sports training, is to improve the performance in the different tournaments held in eastern Cundinamarca and some short tournaments that have during their preparation, in relation to the preparation technical and tactical preparation during 6 months of work. Conclusions: A former a project or approach related to the academic experience of the practitioner, and making the applicability of their knowledge in the field, and that can generate a great change in both the sports club and social level within this community and also as important knowledge acquired by the practitioner during this time of practice.